Penggunaan Coretax dalam Pelaporan PPh 21 pada Rekapitulasi Gaji Karyawan di CV. XYZ - Amalia, Isna Wahyu; Vizandra, Ellyzabeth Putri (Jurnal Riset Manajemen dan Akuntansi, 2026)
This study aims to evaluate effectiveness, efficiency using coretax system by the DJP reporting Income Tax Article 21 based salary recapitulation CV XYZ. Focuses evaluating comparison reporting before and after coretax, impact efficiency Income Tax Article 21 reporting. Against backdrop inefficient reporting, it known that before coretax, CV. XYZ reported through two separate applications, DJP online and e-SPT, process not integrated with salary, prone to input errors, late reporting resulted inefficient process, thus requiring efficient system. With the existence coretax, an evaluation effectiveness supporting efficiency tax reporting administration is needed. The research used qualitative descriptive approach, data collection techniques through observation, interviews, documentation. Data analysis form of narratives, tables, conclusions. This study found use coretax improves efficiency, accuracy, transparency, accountability of PPh 21 tax reporting. Through automation reporting procedures, real-time integration payroll data into DJP, risk administrative errors, late reporting reduced. However, there are obstacles, both technical, systemic, as well as user adaptation, payroll data readiness, which may affect smoothness reporting. Nevertheless, overall use coretax has positive impact improving effectiveness and efficiency tax reporting, tax compliance at CV. XYZ. This article contributes to both science and practice by providing empirical evidence regarding the effectiveness of Coretax. It can be used reference for implementation Coretax by business actors and for development tax digitization policies. This has implications strengthening national tax administration system, can be used basis further research, reference for future technical improvements.